Aplikasi Teknologi Produksi Modern Dan Manajemen Berbasis IT Untuk Meningkatkan Product Quality, Value Added Dan Pemasaran UMKM Tirtha Shanum Malang - Firdaus, Riril Mardiana; Kusufa, Roni Alim Badi’ya; Susanto, Gaguk; R., Yuke Miranda; D., Evangeline Renata (Jurnal ABM Mengabdi, 2025)
The application of modern production technology in the era of Industry 4.0 is the main key to increasing efficiency, quality, and competitiveness in small and medium-sized enterprises. UMKM will obtain good product quality if their production is supported by modern and sophisticated production equipment. In addition, added value in a product also plays an important role in increasing product sales. Good product quality and added value can be seen in good production results, attractive, healthy, hygienic, safe packaging, and having many packaging variants that can be accepted by a wider market. Tirtha Shanum SMEs have not implemented IT-based marketing management so that their products are not widely known by the public. Tirtha Shanum UMKM managed by Arik Exstrada in Kepanjen, Malang, have been operating for about 5 years using young coconut raw materials from local farmers. This business faces obstacles such as limited production equipment, packaging without a trademark, and not utilizing online marketing. Financial management is still mixed with family finances. The business employs 10 casual laborers and produces approximately 110 packages of coconut chips per day (equivalent to 11 kg post-oven), each weighing 100 grams and costing Rp 15,000. Gross daily revenue reaches Rp 1,650,000, with a net profit of approximately Rp 412,500 per day.